Silicon nanowires based inorganic/organic hybrid solar cells - He, Lining. (2013)
As the importance of renewable energy source becomes more apparent, tremendous efforts have been devoted to developing photovoltaics (PV) since solar energy is plentiful and widespread. However, the high production cost of the conventional high-efficiency Silicon (Si) solar cells poses a barrier for solar energy to compete with fossil fuels. This has led to the search of novel solar cells that are low-cost and highly efficient. Recently, there has been significant interest in the study of inorganic/organic hybrid solar cells incorporating Si nanostructures such as Si nanowires (SiNWs) and organic semiconductors, to leverage on the advantages of the former such as high carrier mobility and excellent light trapping capability, and the latter that include low material cost, low temperature and solution based process. The objective of this work is to design, fabricate and characterize SiNWs based inorganic/organic hybrid solar cells. Firstly, various Si surface texturing structures such as SiNWs and SiNWs-on-pyramid have been investigated to form hybrid cells based on bulk crystalline Si, and the choice of organic materials includes conjugated polymer and small molecule. Next, the effects of Si/organic interface treatment on the cell performance have been studied. Finally, hybrid solar cells have been successfully demonstrated on epitaxial Si thin films to bypass the use of costly bulk Si wafer.